Motivasi Mahasiswa UIN Sunan Ampel dalam Pembelajaran Online di Era Pandemi: Tinjauan Perspektif Hamzah B. Uno - Muhammad Thohir; Rizka Dwi Regiyanti; Shofi Nafisah (At-Ta'lim : Media Informasi Pendidikan Islam, 2021)
In the era of the Covid-19 pandemic, the education sector underwent many changes. All learning activities, especially in universities, are transferred online (in the network). These changes have an impact on student learning motivation. This study aims to determine and describe student learning motivation in online learning during the Covid-19 pandemic. Researchers used descriptive research methods with a quantitative approach. The technique used in sampling is purposive sampling with the number of respondents being students of Islamic Education Management at the State Islamic University of Sunan Ampel Surabaya batch 2018. The data collection technique uses a questionnaire. The research subjects consisted of 62 Islamic Education Management students at Sunan Ampel State Islamic University Surabaya batch 2018. This research was conducted by distributing questionnaires via Google Form and then distributing them through WhatsApp groups in the form of links. Data analysis was carried out using the percentage statistical formula. The results of the study concluded that the learning motivation of Islamic Education Management students at UIN Sunan Ampel Surabaya class of 2018 in online learning during the pandemic based on the motivation theory and measurements of Hamzah B. Uno, stated that during online learning, students' motivation tended to be high.